SZCZEGÓLNE FORMY TESTAMENTU W PRAWIE WŁOSKIM - Waszczuk, Jolanta (Zeszyty Prawnicze, 2017)
Particular Forms of a Testament in the Italian Law Summary This article presents a composite regulation regarding particular forms of a testament in the Italian law including its similarities and differences to the Polish law. It discusses the permissibility of drawing up a testament in a particular form. It also presents the process of its drawing up including the persons engaged therein and the procedure of confirming its content. The legal nature of the act a mortis causa is analysed in both legal systems, underlining the subsidiary character of the particular form of a testament and its limited time effect.